Choosing to become a general practitioner - What attracts and what deters? An analysis of German medical graduates′ motives - Tobias Deutsch; Stefan Lippmann; Maximilian Heitzer; Thomas Frese; Hagen Sandholzer (Journal of Family Medicine and Primary Care, 2016)
Background: To be able to counter the increasing shortage of general practitioners (GPs) in many countries, it is crucial to remain up-to-date with the decisive reasons why young physicians choose or reject a career in this field. Materials and Methods: Qualitative content analysis was performed using data from a cross-sectional survey among German medical graduates (n = 659, response rate = 64.2%). Subsequently, descriptive statistics was calculated. Results: The most frequent motives to have opted for a GP career were (n = 74/81): Desire for variety and change (62.2%), interest in a long-term bio-psycho-social treatment of patients (52.7%), desire for independence and self-determination (44.6%), positively perceived work-life balance (27.0%), interest in contents of the field (12.2%), and reluctance to work in a hospital (12.2%). The most frequent motives to have dismissed the seriously considered idea of becoming a GP were (n = 207/578): Reluctance to establish a practice or perceived associated risks and impairments (33.8%), stronger preference for another field (19.3%), perception of workload being too heavy or an unfavorable work-life balance (15.0%), perception of too low or inadequate earning opportunities (14.0%), perception of the GP as a "distributor station" with limited diagnostic and therapeutic facilities (11.6%), perception of too limited specialization or limited options for further sub-specialization (10.6%), rejection of (psycho-) social aspects and demands in general practice (9.7%), and perceived monotony (9.7%). Conclusion: While some motives appear to be hard to influence, others reveal starting points to counter the GP shortage, in particular, with regard to working conditions, the further academic establishment, and the external presentation of the specialty.